Perancangan Sistem Kendali Mesin CNC (Computer Numerical Control) laser Cutting CO2 2 Axis Berbasis Arduino Uno - Lesmana, Bayu; Heryana, Ghany; Jatira (Journal of Applied Mechanical Technology, 2023)
The machining industry, especially machine tools, is currently facing increasingly difficult challenges because this industry is required to produce inexpensive, precise products and fast production times. guaranteed 1/100 mm more and can produce products efficiently. The research to be carried out aims to design control of a CO2 laser cutting machine. So that the machine can work automatically with the control system using the Arduino Uno microcontroller and can run the g-code program with precision and be able to form certain patterns or designs. This laser cnc machine also has several important components including motor drivers, stepper motors, arduino microcontrollers and cnc shields. The operation of this machine uses the ligtburn software. The machine workflow includes a PC (personal computer), g-code, lightburn, driver which will then produce output on the machine in the form of automatic movement.